A method of applying two-pump system in automatic transmissions for energy conservation. (30th June 2015) - Dong, Peng; Liu, Yanfang; Liu, Yang; Xu, Xiangyang
In order to improve the hydraulic efficiency, modern automatic transmissions tend to apply electric oil pump in their hydraulic system. The electric oil pump can support the mechanical oil pump for cooling, lubrication, and maintaining the line pressure at low engine speeds. In addition, the start–stop function can be realized by means of the electric oil pump; thus, the fuel consumption can be further reduced. This article proposes a method of applying two-pump system (one electric oil pump and one mechanical oil pump) in automatic transmissions based on the forward driving simulation. A mathematical model for calculating the transmission power loss is developed. The power loss transfers to heat which requires oil flow for cooling and lubrication. A leakage model is developed to calculate the leakage of the hydraulic system. In order to satisfy the flow requirement, a flow-based control strategy for the electric oil pump is developed. Simulation results of different driving cycles show that there is a best combination of the size of electric oil pump and the size of mechanical oil pump with respect to the optimal energy conservation. Besides, the two-pump system can also satisfy the requirement of the start–stop function. This research is extremely valuable for the forward design of a two-pump system in automatic transmissions with respect to energy conservation and start–stop function.